A review on the strain rate dependency of the dynamic viscoplastic response of FCC metals - Salvado, Francisco C.; Teixeira-Dias, F.; Walley, Stephen M.; Lea, Lewis J.; Cardoso, João B. (Progress in materials science, 2017)
The response of structures and materials subject to impulsive loads remains a field of intense research. The dynamic loading and temperature increase affect the material's mechanical/failure response. For example, strains due to explosive blast will increase at rates from 102 to 104 s-1, leading to regimes of elastic/plastic wave propagation, plane stress and adiabatic deformations. Few constitutive models consider high strain rate effects, however some constitutive approaches that were developed and tested at low strain rate regimes will also be addressed here due to their relevance. Specific reference will be made to strain rate regimes close to 104 s-1, where shock waves may develop. The paper focuses on constitutive models for polycrystalline face-centred-cubic (FCC) metals since their behaviour under high strain rate regimes is not yet fully understood mostly due to path loading dependency. Reference is also made to aluminium alloys since they are widely used in virtually all fields of industry and in armour and protective structures and systems. A basic review of the main theoretical aspects that constitute the basis for most of the constitutive models described is also presented and the main features of each model are thoroughly discussed